2023
DOI: 10.1111/scd.12840
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of dental implants in patients undergoing radiotherapy for head and neck cancer: An umbrella review

Abstract: ObjectiveThe objective of this overview is to evaluate the effectiveness of dental implants placed in patients who underwent radiotherapy for the treatment of head and neck cancer, as well as to assess the methodological quality of the included systematic reviews.MethodsThe study was conducted in four PubMed, Lilacs, Dare Cochrane and Google Scholar databases until July 2022, using the descriptors “Radiotherapy,” “Dental implants,” and “Head and Neck Cancer.” Results: 958 studies were found in the initial sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Camolesi et al [ 32 ], focusing on reports with 5 year data, found 93% vversus 98% implant survival in irradiated and non-irradiated patients, respectively. Zarzar et al [ 33 ] published in 2023 an umbrella review of meta-analyses on the effects of RT on the success of dental implants. They concluded that implantation in irradiated bones had an 86% success rate versus a 95% success rate in normal bone.…”
Section: Resultsmentioning
confidence: 99%
“…Camolesi et al [ 32 ], focusing on reports with 5 year data, found 93% vversus 98% implant survival in irradiated and non-irradiated patients, respectively. Zarzar et al [ 33 ] published in 2023 an umbrella review of meta-analyses on the effects of RT on the success of dental implants. They concluded that implantation in irradiated bones had an 86% success rate versus a 95% success rate in normal bone.…”
Section: Resultsmentioning
confidence: 99%
“…
Dear Editor,We read with great respect the umbrella review by Zarzar et al on the efficacy of implant applications in patients with head and neck cancer (HNC) who have undergone radiotherapy (RT), which is not well-defined and holds many uncertainties. 1 The primary objective of this study was to determine the long-term success rate of dental implants in patients who underwent RT for HNC, while the secondary objective was to examine the incidence of implant-related complications in this patient population. The authors examined 24,996 implants in 5487 patients over one month to 23 years, with an 86.2% success rate for patients who received RT and 95.5% for those who did not.
…”
mentioning
confidence: 99%